(untitled) - Bovée, Courtland L (Boston, 2013)
Business Communication Today provides the cutting-edge communication coverage that prepares readers for real business practice. Understanding the Foundations of Business Communication; Applying the Three-Step Writing Process; Crafting Brief Messages; Supporting Messages with Quality Information; Planning, Writing, and Completing Reports and Proposals; Designing and Delivering Oral and Online Presentations; Writing Employment Messages and Interviewing for Jobs.
Keywords: Business Communication; Giao tiếp kinh doanh; Business -- Skills -- Communications; Kinh doanh -- Kĩ năng -- Giao tiếp